A comprehensive green utilization strategy of lignocellulose from rice husk for the fabrication of high-rate electrochemical zinc ion capacitors. (10th December 2021) - Zhang, Wenli; Jian, Wenbin; Yin, Jian; Zhang, Xiaoshan; Wang, Caiwei; Lin, Xuliang; Qin, Yanlin; Lu, Ke; Lin, Haibo; Wang, Tiejun; Qiu, Xueqing
Abstract: Rice husk is an important biomass residue derived from the production of rice. Rice husk contains silica (10–20 wt%) and lignocellulose (cellulose, 15–25 wt%; lignin, 10–20 wt%). The lignocellulose components in rice husk are potential carbon sources for functional carbon materials. In this work, we propose a general comprehensive green utilization strategy for the preparation of lignin-derived hierarchical porous carbon (LHPC) and cellulose-paper-based separator using the lignin and cellulose components inside rice husk, respectively. The obtained LHPC and cellulose paper separators were used as pivotal components for the fabrication of high-rate electrochemical zinc ion capacitors. Meanwhile, the silica and potassium sources in this comprehensive route were recycled as nano-sized SiO2 particles and pure KCl powders. This work constitutes a general route for the green utilization of rice husk biomass. This work opens a green avenue for the effective utilization of renewable biomasses to develop functional carbon materials and pivotal components of electrochemical energy storage devices. Graphical abstract: Image 1 Highlights: A green comprehensive utilization route is invented to utilize rice husk. Lignocellulose in rice husk is converted into separator and porous carbon cathode. Nano-SiO2 and KCl are recycled from this comprehensive utilization process. The assembled electrochemical zinc ion capacitor shows high rate capability.